OMISSION TRANSFORMATION AS A MEANS OF REPRODUCING OBSOLETE LEXICON IN ARTISTIC TRANSLATION - Lasinska, Tatiana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is dedicated to the study and analysis of omission transformation methods as a crucial tool for reproducing obsolete vocabulary in artistic translation. Generally, words and expressions that have become obsolete in native speakers' communication are lost in modern discourse, yet they hold valuable cultural heritage. The research is grounded in the analysis of specific examples of such vocabulary and the exploration of its potential applications in a new context. The article examines various examples and techniques of omission transformation that can be effectively employed to refresh and enrich contemporary language practice in artistic translation. The author of the article focuses on how the use of such an approach can contribute to preserving integral elements of the original work in translation, ensuring its comprehensibility and relevance for a modern audience.________________References:• Scott, W. Ivanhoe (Ware, Wordsworth Edition Ltd, 1995), 390.• Skott, Ajvengo, per. z angl. I. Davydenko (Kyi’v, Krai’na Mrij, 2014), 400.
Keywords: omission transformation, obsolete lexicon, artistic translation, reproduction of lexical material, cultural adaptation, creative translation.Keywords: omission transformation, obsolete lexicon, artistic translation, reproduction of lexical material, cultural adaptation, creative translation